Phytochemical Characterization and Comparative Analysis of Cycloartane-Type Triterpenes in Astragalus adsurgens and Astragalus membranaceus - Zhou, Guanglian; Chen, Yin; Xu, Bingyan; Peng, Guoqing; Wang, Li; Huang, Jian-Ping; Yu, Zhiyin; Huang, Sheng-Xiong (Planta Medica, 2025)
Astragalus adsurgens, a significant forage plant cultivated in arid regions of northwest China, remains underexplored for its triterpenoid saponins and medicinal properties compared to the extensively studied Astragalus membranaceus. To explore the phytochemical profile of A. adsurgens for its potential application in the medical field, we employed ultra-pressure liquid chromatography coupled with a tandem mass spectrometry-based method to identify cycloartane-type triterpenes. Eventually, five new cycloartane-type triterpenoids, adsurgosides A – D (1 – 4) and 3-methyl-3,4-seco-cyclostellanol (5), together with two known analogs, cycloastragenol (6) and cyclopycanthogenin (7), were isolated from the roots of A. adsurgens. Their structures were elucidated using 1D and 2D NMR analyses in combination with HRESIMS data. Additionally, a comparative study on the distribution patterns of these compounds revealed qualitative and quantitative variations between A. adsurgens and A. membranaceus. Our findings not only identified an alternative plant for isolating cycloartane-type triterpenoids but also offer new insights into the chemical properties of A. adsurgens.
Keywords: Fabaceae; Astragalus adsurgensb; Astragalus membranaceus; chemical constituents; cycloartane-type triterpenoids; target metabolites analysis